2022
DOI: 10.1136/bmjsem-2022-001330
|View full text |Cite
|
Sign up to set email alerts
|

Period prevalence of SARS-CoV-2 infections and willingness to vaccinate in Swiss elite athletes

Abstract: Objectives(1) To assess the period prevalence of SARS-CoV-2 infections and willingness to vaccinate in Swiss elite athletes and (2) to evaluate whether sociodemographic and sport-related characteristics were associated with infection of SARS-CoV-2 in athletes.MethodsA total of 1037 elite athletes (Mage=27.09) were surveyed in this cross-sectional study. They were asked whether they had been infected with SARS-CoV-2 and whether they would like to be vaccinated. Characteristics of a possible COVID-19 illness wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Indeed, in this study, the occurrence of infection was the highest among water polo players and artistic swimmers while the lowest among open water swimmers. This aligns with reports of higher transmission of SARS-CoV-2 infection in team sports 35 , 36 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, in this study, the occurrence of infection was the highest among water polo players and artistic swimmers while the lowest among open water swimmers. This aligns with reports of higher transmission of SARS-CoV-2 infection in team sports 35 , 36 .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, most studies have reported mild to moderate COVID-19 symptoms in athletes 32 , 35 , 39 41 . In our findings, the main symptoms were headache, fever and cough.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation